The Influence of Print Media (Leaflets) on Adolescent Girls' Knowledge of Handling Dysmenorrhea in Junior High Schools - Etti Susana Marito; Owusu Danso; Niphon Watada (Journal of Health Innovation and Environmental Education, 2024)
Purpose of the study: This study aims to determine the influence of print media (leaflets) on the knowledge of grade VIII female adolescents about handling dysmenorrhea. Methodology: The type of research that will be used in this study is by using the pre-experimental design method, with the type of pre-test and post-test one group design. The population in this study were 65 female adolescents in grade VIII, of which 40 people experienced dysmenorrhea and 25 people did not experience dysmenorrhea. The sample in this study was 40 female adolescents in grade VIII who experienced dysmenorrhea. Main Findings: The results of the study showed that there was an influence of printed media (leaflets) on the knowledge of female adolescents in grade VIII about dysmenorrhea with a Z coefficient value of -3.945 and an Asym.Sig (p value) of 0.0000 with an Asym.Sig value (p value) <0.05. Novelty/Originality of this study: This study revealed that printed media in the form of leaflets can be an effective educational method in increasing the understanding of adolescent girls regarding the management of dysmenorrhea in junior high schools.